2022
DOI: 10.3390/metabo12111124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Softening Dry Food with Water on Stress Response, Intestinal Microbiome, and Metabolic Profile in Beagle Dogs

Abstract: Softening dry food with water is believed to be more beneficial to the intestinal health and nutrients absorption of dogs by some owners, but there appears to be little scientific basis for this belief. Thus, this study aimed to compare feeding dry food (DF) and water-softened dry food (SDF) on stress response, intestinal microbiome, and metabolic profile in dogs. Twenty healthy 5-month-old beagle dogs were selected and divided into two groups according to their gender and body weight using a completely random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…In terms of flora composition, both temporal and energy level factors influenced the profiles of the genus and phylum levels and the number of ASVs. Similar findings have been obtained in canine studies on the relationship between food and the gut microbiota [93][94][95] and related studies have also demonstrated that Fusobacterium and Clostridium appear to be very strongly associated with the administration of raw-meat-based diets to cats and dogs [96].…”
Section: Discussionsupporting
confidence: 85%
“…In terms of flora composition, both temporal and energy level factors influenced the profiles of the genus and phylum levels and the number of ASVs. Similar findings have been obtained in canine studies on the relationship between food and the gut microbiota [93][94][95] and related studies have also demonstrated that Fusobacterium and Clostridium appear to be very strongly associated with the administration of raw-meat-based diets to cats and dogs [96].…”
Section: Discussionsupporting
confidence: 85%
“…Abrupt environmental accidents such as sudden noise [ 14 ] and falling objects [ 15 ] usually result in panic and fear in pets. Even some common feeding practices, such as water-softened dry food can present stress in pets [ 16 ]. Psychological stress can occur when space allowance for activity and behavioral needs are not met [ 17 , 18 ].…”
Section: Causes Of Stress In Petsmentioning
confidence: 99%
“…Associations between cortisol and gut microbial abundance in dogs have been already explored [2,38]. Briefly, in a randomized study of 20 5-monthold beagles examining the safeness of softening dog food with water, dogs that consumed softened dog food had higher levels of cortisol and higher levels of pathogenic bacteria including Enterococcus [38]. In our prior study, we found that cortisol decreased in the dogs 28 days after supplementation administration [14].…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, the ASVs belonging to Dorea longicatena may have a role in levels of cortisol, the hormone that responds to stress, in the dogs. Associations between cortisol and gut microbial abundance in dogs have been already explored [2,38]. Briefly, in a randomized study of 20 5-monthold beagles examining the safeness of softening dog food with water, dogs that consumed softened dog food had higher levels of cortisol and higher levels of pathogenic bacteria including Enterococcus [38].…”
Section: Discussionmentioning
confidence: 99%